Effects of Periodontal Endoscopy-Assisted Nonsurgical Treatment of Periodontitis: Four-Month Results of a Randomized Controlled Split-Mouth Pilot Study. (17th January 2022) - Graetz, Christian; Sentker, Johanna; Cyris, Miriam; Schorr, Susanne; Springer, Claudia; Fawzy El-Sayed, Karim M.
Abstract : Objective . Although the therapeutic effects of nonsurgical periodontal therapy (NSPT) are well established, the clinical benefits of the additional use of periodontal endoscopy (PE) remain controversial. Therefore, this randomized controlled split-mouth pilot study evaluated the effect of NSPT using PE versus NSPT without n PE on bleeding on probing (BOP) in sites with probing depth (PD)≥4 mm (primary outcome), PD, clinical attachment level (CAL), number of hard deposits (HDs), and treatment time per tooth (TrT). Methods . Two calibrated operators performed NSPT in twenty periodontitis patients, randomized into two quadrants for PE or n PE treatment. BOP, PD, and CAL were recorded at the first visit for NSPT ( T 0) and during reevaluation ( T 1: mean (SD) 119.7 (24.6) days after T 0). The average TrT and the number of sites with HDs were documented at T 0. Results . For BOP, no significant differences were found at the patient's level (10/10 (male/female); aged 54.3 (10.9) years) neither within or between the groups. At tooth surface level, a lower number of surfaces with BOP p = 0.026 was observed in n PE. CAL and PD improved significantly during NSPT in both groups p ≤ 0.001, with higher PD reduction p < 0.001 and CAL gain p < 0.001 in n PE. There are significantly longer TrT p < 0.001 and more surfaces with subgingival HDs evident in PE at T0 p = 0.001 . Conclusion . Whereas subgingival HDs can be visually detected with PE during NSPT, no additional clinical benefits regarding BOP, PD, or CAL were notable compared to conventional systematic periodontal instrumentation. Additionally, PE-assisted NSPT required a longer treatment time.